O movimento operário e sindical em Passo Fundo (1900-1964) : história e política - Batistella, Alessandro (2007)
This paper has as main goal to analyze the worker and syndicalism movement in Passo Fundo from 1900 to 1964, protruding that the study s main goal are the urban workers and their organizations. For suchlike proposes, is necessary to emphasizes the main differences and similarities between the national and regional process, above all in the political matter, it will be ponder about the politician-ideological chains present in the local syndicalism, about the strikes and the popular movements occurred in the focused years and, finally, about the major national social-political event implications in the worker and syndicalism movement in Passo Fundo